Examining the role of road safety audits worldwide: exploring road safety expert's opinions. Issue 1 (2nd January 2023) - AlHamad, Souad; Almallah, Mustafa; Naser, Mohammad N.; Alhajyaseen, Wael K. M.; de Roos, Michael Philip
Abstract: Road safety audit (RSA) is a method used to proactively identify safety risks in road projects from planning, design, and construction stages. The effectiveness of the implementation of RSAs varies across the globe. This paper provides an understanding of road safety auditor's opinions and attitudes by using data collected from an online questionnaire filled by 408 road safety experts with varying demographic and technical backgrounds. Results demonstrated that majority of respondents agreed that RSA is an effective tool to improve road safety. Compared to high-income countries, respondents from low- and middle-income countries had less knowledge about RSA and less access to RSA guidelines. The results also indicate that many road safety auditors have a misunderstanding of the independence requirement for conducting RSA. The results of this paper can be used to inform and develop improved guidance to improve RSA generally and promote RSA as an effective road safety engineering tool.